Rendemen dan kualitas minyak nilam (Pogostemon cablin Benth.) dari Kalimantan Timur serta analisis tekno-ekonominya - Nur Amaliah; Krishna Purnawan Candra; Viky Bayu Parytha; Arif Kurniawan; Tazri Amrullah; Bernatal Saragih; Hudaida Syahrumsyah; Yuliani Yuliani (AGROINTEK, 2022)
This study aimed to determine the patchouli oil (PO) business in the province of East Kalimantan based on data on the yield and quality of PO produced from several PO production centers in East Kalimantan. Bangun Rejo Village in Kutai Kartanegara Regency, Sepaku I Village and Argo Mulyo Village in Penajam Paser Utara Regency were selected as samples in this study. PO extraction from plant samples from each village was carried out using a laboratory-scale wet distillation method (3 kg leaves, branches) per batch. Each batch was carried out with six replications using different samples. The sample of PO produced by farmers was used as a control. The results showed that the yield of PO from the three villages reached 1.25-1.76%, while the quality of the oil showed an acid number of 2.407-4.747%, ester number 11.843-16.768%, PO content 33.670-43.693%, iron content 1.096-8.538 mg/kg, density 0.614-0.822 g/cm3, refractive index 1.509 nD20 and light-yellow to yellow. PO produced by farmers has an acid number of 6.311-11.920%, ester number 16.269-19.822%, ethanol solubility 1:5-1:9, patchouli alcohol content 31.96-40.89%, iron content 0.460-1.105 mg/kg, density 0.946-1,509 g/cm3, refractive index 1.508-1.510 nD20 and yellow to dark yellow in colour. Techno-economic analysis (using laboratory-scale extraction yield data) shows that PO refining business in the two villages is feasible to be carried out with B/C values of 3.62 and 6.37 for Sepaku I Village and Bangun Rejo Village. Still, it is not feasible for Argo Mulyo (B/C value of 0.842)